2020
DOI: 10.1007/s10924-020-01954-x
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Ascorbyl Palmitate in Zein by Electrospinning Technique

Abstract: In this study, ascorbyl palmitate was encapsulated in electrospun zein fibers at different loading levels (2.5%w/v, 5%w/v and 10% w/v). HPLC, SEM, FTIR, XRD, DSC and BET characterized the resulting electrospun zein fibers containing ascorbyl palmitate. Results indicated that the diameters of electrospun zein fibers increased with increasing concentration of ascorbyl palmitate. The physical status of ascorbyl palmitate in electrospun zein fibers was determined by X-ray diffraction (XRD), and differential scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…It is reported that the most significant parameter in controlling the morphology and diameter of electrospun fibers during electrospinning process is the concentration of solution. With increasing concentration, the diameter of the fiber also increases; this is probably due to the greater resistance of the high concentration solutions to be stretched toward the collector (Heydari‐Majd et al., 2019; Miri et al., 2020; Teo & Ramakrishna, 2006). Another reason may be attributable to the electrical conductivity of the solutions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is reported that the most significant parameter in controlling the morphology and diameter of electrospun fibers during electrospinning process is the concentration of solution. With increasing concentration, the diameter of the fiber also increases; this is probably due to the greater resistance of the high concentration solutions to be stretched toward the collector (Heydari‐Majd et al., 2019; Miri et al., 2020; Teo & Ramakrishna, 2006). Another reason may be attributable to the electrical conductivity of the solutions.…”
Section: Resultsmentioning
confidence: 99%
“…The AFM images show the tubular shape of electrospun fibers better than SEM images. It seems that the tubular‐shaped fibers are formed when a highly volatile solvent system such as acetic acid is used for electrospinning (Miri et al, 2020). It could be concluded that encapsulation of rosemary essential oil did not alter the morphology of zein electrospun fibers, but the electrospun fiber diameter increased with increasing essential oil concentration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chitin, chitosan, , and scaffolds derived from hyaluronic acid are also notable choices. Protein-based polymers such as gelatin, , collagen, zein, , and soy are employed for creating scaffolds that closely mimic the extracellular matrix (ECM). The advantage of natural polymers lies in their ability to dissolve without aggressive chemical solvents.…”
mentioning
confidence: 99%